(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
This research focuses on studying the interactions between a closely spaced wave energy converter (WEC) array with an adaptable hydraulic power take-off (PTO) system. The boundary element method is used to extract the hydrodynamic and hydrostatic coefficients, while the power extraction and hydrodynamic behaviour of the array are simulated in irregular waves with a mixed frequency-time-domain (MFT) model to include the nonlinear PTO forces of each array element. The interactions between floaters are assessed and the influence of adaptability on the behaviour of the total array and its elements in comparison to single floater performance (i.e., the q factor) is analysed. The differences in performance of the WEC array are assessed with three levels of adaptability: no adaptability, adaptability per sea state and adaptability per incoming wave.